Treatment of waste gas contaminated with dichloromethane using photocatalytic oxidation, biodegradation and their combinations - Fares Almomani (12585685) (2021)
The treatment of waste gas (WG) containing dichloromethane (DCM) using advanced oxidation processes (AOPs) [UV and UV-TiO2], biological treatment (BT), and their combination (AOPs-BT) was tested. AOP tests were performed in an annular photo-reactor (APHR), while BT was conducted in a continuous stirred tank bioreactor (CSTBR). The effects of gas flow rate (Qgas), inlet DCM concentration ([DCM]i), residence time (τ), photocatalyst loading (PH-CL) and % relative humidity (% RH) on the AOPs performance and the removal of DCM (Mr) were studied and optimized. The UV process exhibited Mr ≤ 12.5 % for tests conducted at a [DCM]i ≤ 0.45 g/m3, Qgas of 0.12 m3/h and τ of 27.6 s, respectively, and < 4 % when the [DCM]i ≥ 4.2 g/m3. The UV-TiO2 achieved a Mr ≥ 71 ± 1.5 % at Qgas of 0.06 m3/h, [DCM]i of 0.45 g/m3, τ of 55.2 s, PH-CL of 10 g/m2, and %RH of 50, respectively. The BT process removed ∼97.6 % of DCM with an elimination capacity (EC) of 234.0 g/m3·h. Besides, the high Mr of ∼98.5 % in the UV-BT and 99.7 % in the UV-TiO2-BT processes confirms AOPs-BT as a promising technology for the treatment of recalcitrant compounds present in WG. Other Information Published in: Journal of Hazardous Materials License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jhazmat.2020.123735